Nanotechnology for biomedical applications - Gopi, Sreerag; Balakrishnan, Preetha 1986-; Mubarak, Nabisab Mujawar (Materials horizons: from nature to nanomaterials, 2022)
This book provides an overview of the use of nanoparticles, carbon-nanotubes, liposomes, and nanopatterned flat surfaces for specific biomedical applications. This book explains the chemical and physical properties of the surface of these materials that allow their use in diagnosis, biosensing and bioimaging devices, drug delivery systems, and bone substitute implants. The toxicology of these particles is also discussed in the light of a new field referred to as nanotoxicology in this book. This book will be useful for engineers, researchers and industry professionals primarily in the fields of polymer science and engineering, materials science, surface science, nanocatalysis, biotechnology and biomedicine